Development Based Blended Learning Model Type Flipped Classroom of Edmodo to Learning Achievement Sociology Improve Students' at SMA Negeri 1 Terbanggi Besar Class X - Agrina Darwis; Rangga Firdaus; Muhammad Nurwahidin (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
This study aims to develop an Edmodo-based blended learning model for improving student achievement in Sociology subjects at SMA Negeri 1 Terbanggi Besar and reviewing the effectiveness and efficiency of the learning process using the developed learning design products. This type of research is R & D using 4D model development. The instruments in this study were expert validation sheets, teacher and student responses questionnaire sheets, and learning implementation observation sheets. The data analysis techniques used in this research are descriptive analysis, expert validation data analysis, and test data analysis. The results of the research based on the data and discussion concluded that the product for developing the Edmodo-based blended learning model design to improve student learning achievement was declared valid, attractive, efficient and effective based on the assessments of experts, teachers and students. Suggestions given at least for the reader can develop into other aspects of the character or other subjects.